Mutation of the Light-Induced Yellow Leaf 1 Gene, Which Encodes a Geranylgeranyl Reductase, Affects Chlorophyll Biosynthesis and Light Sensitivity in Rice - Zhou, Yong; Gong, Zhiyun; Yang, Zefeng; Yuan, Yuan; Zhu, Jinyan; Wang, Man; Yuan, Fuhai; Wu, Shujun; Wang, Zhiqin; Yi, Chuandeng; Xu, Tinghua; Ryom, MyongChol; et al. (PLOS ONE, 2013)
Chlorophylls (Chls) are crucial for capturing light energy for photosynthesis. Although several genes responsible for Chl biosynthesis were characterized in rice (Oryza sativa), the genetic properties of the hydrogenating enzyme involved in the final step of Chl synthesis remain unknown. In this study, we characterized a rice light-induced yellow leaf 1-1 (lyl1-1) mutant that is hypersensitive to high-light and defective in the Chl synthesis. Light-shading experiment suggested that the yellowing of lyl1-1 is light-induced. Map-based cloning of LYL1 revealed that it encodes a geranylgeranyl reductase. The mutation of LYL1 led to the majority of Chl molecules are conjugated with an unsaturated geranylgeraniol side chain. LYL1 is the firstly defined gene involved in the reduction step from Chl-geranylgeranylated (ChlGG) and geranylgeranyl pyrophosphate (GGPP) to Chl-phytol (ChlPhy) and phytyl pyrophosphate (PPP) in rice. LYL1 can be induced by light and suppressed by darkness which is consistent with its potential biological functions. Additionally, the lyl1-1 mutant suffered from severe photooxidative damage and displayed a drastic reduction in the levels of α-tocopherol and photosynthetic proteins. We concluded that LYL1 also plays an important role in response to high-light in rice.